The Language of the Spirit of the Spirit in the Language: a preliminairy Discussion of Glossolalia Practices in some Botswana Chruches - Chebanne, A. M. (Scriptura: Journal for Biblical, Theological and Contextual Hermeneutics, 2006)
Glossolalia, or glossia, a scientific term from Greek meaning "language of language" is used in the New Testament to refer to what Paul refers to as "tongue(s)" or speaking therefore. The original Greek texts make the distinction between the glossolalia phenomenon and the experience of Pentecost recorded in Acts 2, which the Greek texts qualify as xenoglossia, simply meaning foreign or strange tongue(s). While biblically and linguistically xenoglossia would make sense to interest oneself in its analysis, the question of glossolalia has always eluded logic and analysis, and consequently its practice in the Church has often been a subject of controversy. This paper reports on the investigation undertaken in some Christian Churches in and around Gaborone where glossolalia manifestations have been observed. The discussion will attempt in the first instance to report on the way Churches understand this phenomenon and how they integrate it within their worship service. It will also submit that there is no one form of this phenomenal manifestation, but there are all types - religious / spiritual, eulogical, and pathological and all using some intelligible utterances. All may be found within the Church, and even outside among African traditional healers. Same phenomenon, but the same spirit? An attempt will be made to provide the answer.
Keywords: Church in Botswana; Glossolalia